A study on automated self-ordering menu using the lens of technology acceptance model : a focus on Klang Valley Restaurant - Baharuddin, Muhammad Hasbi (2012)
The basic problem in the food service industry is that restaurants are not realizing efficiencies that would result from better applications of technology in their daily operations. Labor rates are rapidly increasing every now and then and it is difficult to find employees in the middle of the busy restaurant. Thus the introductions of Automated Self-ordering menu technologies to the restaurant help to overcome the problem. Automated Self-ordering Menu are "technological interfaces that enable customers to produce a service independent of direct service-employee involvement. Consumers' adoption of new information technology has been a central concern to many researchers and practitioners owing to its importance in technology diffusion. Based on the underlying knowledge-based view perspective, this paper aims to empirically examine the contribution of the dimensions of Automated Self-ordering Menu using the lens of Technology Acceptance Model, focusing on Klang Valley restaurant. Approach: The theoretical model and hypotheses in this study were tested using empirical data gathered from local restaurant that utilizing Automated Self-ordering Menu, through survey questionnaires were analyzed using the correlation coefficients and linear regression analyses. Results: The results revealed that perceived usefulness and perceived ease of use as two critical elements of knowledge characteristics have significant affects on the customer readiness and customer adoption of utilizing Automated Self-ordering Menu. Conclusion: The study has bridged the literature gaps in such that it provides empirical evidence of a positive significant correlation between the technology acceptance model and its two din1ensions: readiness and adoption of customer toward utilizing Automated Self-ordering Menu.